Interaction between teacher and nursing students in the classroom setting and the clinical performance in the Nursing Campus Maharajgunj, Kathmandu, Nepal - Nani Maiya Shrestha (Chulalongkorn University, 2013)
Thesis (M.Sc.)--Chulalongkorn University, 1990